‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Time-lapse resistivity imaging and self-potential monitoring of experimentally induced saline intrusion in coastal aquifer sands - Jesús F. Águila; Thomas S.L. Rowan; Mark C. McDonnell; Raymond Flynn; Shane Donohue; Matthew D. Jackson; Adrian P. Butler; Gerard A. Hamill; Eric M. Benner; Georgios Etsias (Science of The Total Environment, 2025)

Reflex impairment as a predictor of mortality in Panulirus argus: Implications for the live export market - Erica P. Ross; Casey B. Butler; Carly M. Hannah; Thomas R. Matthews (Fisheries Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The value of adding black carbon to community monitoring of particulate matter - Rebecca A. Sugrue; Chelsea V. Preble; James D.A. Butler; Alaia J. Redon-Gabel; Pietro Marconi; Karan D. Shetty; Lee Ann L. Hill; Audrey M. Amezcua-Smith; Boris R. Lukanov; Thomas W. Kirchstetter (Atmospheric Environment, 2024)

Complementary and Inducible creERT2 Mouse Models for Functional Evaluation of Endothelial Cell Subtypes in the Bone Marrow - Michael G. Poulos; Pradeep Ramalingam; Agatha Winiarski; Michael C. Gutkin; Lizabeth Katsnelson; Cody Carter; Laurence Pibouin-Fragner; Anne Eichmann; Jean-Leon Thomas; Lucile Miquerol; Jason M. Butler (Stem Cell Reviews and Reports, 2024)
In the adult bone marrow (BM), endothelial cells (ECs) are an integral component of the hematopoietic stem cell (HSC)-supportive niche, which modulates HSC activity by producing secreted and membrane-bound paracrine signals. Within the BM, distinct vascular arteriole, transitional, and sinusoidal EC subtypes display unique paracrine expression profiles and create anatomically-discrete microenvironments. However, the relative contributions of vascular endothelial subtypes in supporting hematopoiesis is unclear. Moreover, constitutive expression and off-target activity of currently available endothelial-specific and endothelial-subtype-specific murine cre lines potentially confound data analysis and interpretation. To address this, we describe two tamoxifen-inducible cre -expressing lines, Vegfr3-creER T2 and Cx40-creER T2 , that efficiently label sinusoidal/transitional and arteriole endothelium respectively in adult marrow, without off-target activity in hematopoietic or perivascular cells. Utilizing an established mouse model in which cre -dependent recombination constitutively-activates MAPK signaling within adult endothelium, we identify arteriole ECs as the driver of MAPK-mediated hematopoietic dysfunction. These results define complementary tamoxifen-inducible creER T2 -expressing mouse lines that label functionally-discrete and non-overlapping sinusoidal/transitional and arteriole EC populations in the adult BM, providing a robust toolset to investigate the differential contributions of vascular subtypes in maintaining hematopoietic homeostasis. Graphical Abstract

Carbon footprint assessment of a wood multi-residential building considering biogenic carbon - Claudiane M. Ouellet-Plamondon; Livia Ramseier; Maria Balouktsi; Laetitia Delem; Greg Foliente; Nicolas Francart; Antonio Garcia-Martinez; Endrit Hoxha; Thomas Lützkendorf; Freja Nygaard Rasmussen; Bruno Peuportier; Jarred Butler; et al. (Journal of Cleaner Production, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Engineered biosynthesis of cyclotides - Thomas N. G. Handley; Hyon-Xhi Tan; Malcolm T. Rutledge; Hans Henning Brewitz; Joel D. A. Tyndall; Torsten Kleffmann; Margi I. Butler; Russell T. M. Poulter; Sigurd M. Wilbanks (New Zealand Journal of Botany, 2020)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

2nd International Conference on Progressive Multifocal Leukoencephalopathy (PML) 2015: JCV virology, progressive multifocal leukoencephalopathy pathogenesis, diagnosis and risk stratification, and new approaches to prevention and treatment - Andriani C. Patera; Scott L. Butler; Paola Cinque; David B. Clifford; Robert Elston; Robert L. Garcea; Eugene O. Major; Dejan Pavlovic; Ilse S. Peterson; Anne M. Ryan; Kenneth L. Tyler; Thomas Weber (Journal of NeuroVirology, 2015)

Agronomic factors affect powdery scab of potato and amounts of Spongospora subterranea DNA in soil - Farhat A. Shah; Richard E. Falloon; Ruth C. Butler; Ros A. Lister; Steve M. Thomas; Denis Curtin (Australasian Plant Pathology, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Physiological and functional evaluation of healthy young and older men and women: design of the European MyoAge study - Jamie S. McPhee; Jean-Yves Hogrel; Andrea B. Maier; Enn Seppet; Olivier R. Seynnes; Sarianna Sipilä; Roberto Bottinelli; Yoann Barnouin; Astrid Y. Bijlsma; Helena Gapeyeva; Thomas M. Maden-Wilkinson; Carel G. Meskers; et al. (Biogerontology, 2013)

Structural limits on force production and shortening of smooth muscle - Marion J. Siegman; Sandra Davidheiser; Susan U. Mooers; Thomas M. Butler (Journal of Muscle Research and Cell Motility, 2013)

A force-activated kinase in a catch smooth muscle - Thomas M. Butler; Marion J. Siegman (Journal of Muscle Research and Cell Motility, 2011)

Twitchin as a regulator of catch contraction in molluscan smooth muscle - Daisuke Funabara; Satoshi Kanoh; Marion J. Siegman; Thomas M. Butler; David J. Hartshorne; Shugo Watabe (Journal of Muscle Research and Cell Motility, 2006)

Phosphorylation of a high molecular weight (∼600 kDa) protein regulates catch in invertebrate smooth muscle - Marion J. Siegman; Susan U. Mooers; Chenqing Li; Srinivasa Narayan; Laura Trinkle-Mulcahy; Shugo Watabe; David J. Hartshorne; Thomas M. Butler (Journal of Muscle Research and Cell Motility, 1997)